ELITE SOCCER'S LOWER LIMBS EXPLOSIVE STRENGTH ASYMMETRY. Issue 10 (10th June 2013) - Zahalka, Frantisek; Maly, Tomas; Mala, Lucia; Teplan, Jaroslav; Gryc, Tomas; Vaidova, Eva; Hank, Mikulas; Buzek, Mario
Abstract : Background: A vertical jump is one of essential motor skills in many sports (Vanezis & Lees, 2005). Monitoring and description of vertical jumps is based on both external movement structure and explosive strength of lower limbs as a basic driving impulse for its performance. Explosive strength is one of the most important components for the body increasing and vertical jump (Aragon, 2000). Methods: The research group consisted of elite soccer players (n=138, age=25, 1±4, 7 years, height=184, 2±7, 2 cm, weight=79, 7±8, 1 kg). For recording force effect of lower limbs on the surface, two force platforms Kistler B8611A (KISTLER Instrumente AG, Switzerland) were used. All participants performed three types of a vertical jump, T1–countermovement jump with arms included, T2–countermovement jump with arms excluded, T3–squat jump. Evaluation parameters were: high of the jump (cm), maximal strength produced by separate lower limb FmaxR(L) and strength impulse produced by separate lower limb during the take off (Ns-1). Results: The heights of the jumps were CMJ-FA=42.83±4.88 cm, CMJ=37.55±4.18 cm a SQJ=35.97±3.97cm. Maximal strength produced by separate lower limb was recalculated by dividing to weight of every player as a strength for one kilogram; FmaxPT1=1.32±0.11 N.kg-1 resp. FmaxLT1=1.27±0.11 N.kg-1; FmaxPT2=1.33±0.14 N.kg-1 resp. FmaxPT2=1.28±0.16 N.kg-1; FmaxPT3=1.12±0.12 N.kg-1 resp. FmaxLT3= 1.09±0.09 N.kg-1. The level of asymmetry was evaluated by percentage difference between maximal strength of right or left lower limb per one kilogram of boy weight. Percentage difference between maximal strength was T1=5.86±4.58%; T2=9.61±7.92, T3=5.47±6.49%. Evaluation of lower limbs asymmetry by help of strength impulse using the take off was T1=9.91±10.49 N.s-1, T2=8.55±7.34 N.s-1, T3=5.69±4.73 N.s-1. Discussion/Conclusions: The best results were achieved in the first type of the vertical jump (T1). Results of the countermovement jump without arm swing (T2) and squat jump without arm swing (T3) are more comparable, although it could be expected that squat position could improve the height of absolute value of the vertical jump. The biggest asymmetry by maximal strength point of view was found in the jump T2. Jumps T1 and T2 had asymmetry by maximal strength point on were similar and the absolute value was only half according to jump T1 asymmetry. The biggest asymmetry by strength impulse was in the jump T1, rest jump's aszmmetry were lower (T2-13%; T3-42%). Project was supported: MSM 0021620864, GACR P407/11/P784, PRVOUK 38.